A Linear Temperature-to-Differential-Current Converter - Pookaiyaudom, S.; Watanachaiprateep, C. (My University, 1979)
A simple circuit is proposed as a linear temperature-to-differential current converter. Large and accurate conversion rate can be easily obtained. An immediate application has also been proposed. © 1979 IEEE